The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.macromol.1c01267
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Doped α-Oligo- and Polyfurans: Highly Luminescent Hybrid Materials, Color-Tunable through the Doping Density

Abstract: Doping of π-conjugated polymers or molecular compounds with trivalent boron atoms has recently emerged as a viable strategy to produce new materials with intriguing properties and functions. The combination of boron with furan moieties has been only scarcely explored so far, although the resulting furan-based materials have several notable features, including favorable optoelectronic properties and improved sustainability. Herein, we investigate the doping of α-polyfurans with a varying number of boron atoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 151 publications
0
5
0
Order By: Relevance
“…The higher molecular weight sample of PFB3T’‐B showed multiple series of peaks due to one or two additional thiophene units, which still primarily correspond to cyclic products. The formation of cyclic rather than linear conjugated polymers has been reported for Suzuki‐Miyaura polycondensation reactions with suitably shaped (kinked) monomers, [19] but has to our knowledge only rarely been observed [5l,14e,f] in Stille polymerization of thiophenes. In our case, cyclic tetramers and pentamers are obtained preferentially, possibly also aided by the bent shape of the dithienylborane building blocks (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…The higher molecular weight sample of PFB3T’‐B showed multiple series of peaks due to one or two additional thiophene units, which still primarily correspond to cyclic products. The formation of cyclic rather than linear conjugated polymers has been reported for Suzuki‐Miyaura polycondensation reactions with suitably shaped (kinked) monomers, [19] but has to our knowledge only rarely been observed [5l,14e,f] in Stille polymerization of thiophenes. In our case, cyclic tetramers and pentamers are obtained preferentially, possibly also aided by the bent shape of the dithienylborane building blocks (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, boron-containing conjugated π-systems have frequently been employed to construct color-tunable π-conjugated polymers. [84][85][86][87] In a different approach, Wang, Li and co-workers demonstrated that multicolor emission that is dependent on the degree of polymerization can be achieved by chromophore assembly of nonconjugated side-chain functionalized polymers PB8 (Figure 3B). [88] They utilized a stimulus-responsive boron chromophore that exhibits different emission colors in its closed (red, tetracoordinate boron) and open conformation (blue, tricoordinate boron).…”
Section: Assembly Of Luminescent Boron Polymersmentioning
confidence: 99%
“…The boron (B) atom is a special member of the main-group elements. Implanting B atom with an empty p-orbital endowed OCPs with intriguing optoelectronic properties that are distinct from other OCPs. , For example, OCPs with a tricoordinate B-center exhibited excellent toxic material (F/CN anions and amines) sensing properties. , Introducing tricoordinate or tetracoordinate B-building blocks with strong electron-withdrawing characteristics into polymeric backbones efficiently lowered the LUMOs of OCPs, consequently enhancing the electron-accepting and electron-transporting characteristics. , …”
mentioning
confidence: 99%